2021
DOI: 10.1177/02841851211041820
|View full text |Cite
|
Sign up to set email alerts
|

BLADE turbo gradient- and spin-echo in the assessment of sinonasal lesions: a comprehensive comparison of image quality in readout-segmented echo-planar imaging

Abstract: Background A two-dimensional turbo gradient-echo and spin-echo diffusion-weighted pulse sequence with a non-Cartesian BLADE trajectory (TGSE BLADE) can eliminate image artifacts and distortion with clinically acceptable scan times. This process has the potential to overcome the shortcomings of current diffusion-weighted imaging (DWI) techniques, especially in the sinonasal region. Purpose To investigate the feasibility of TGSE BLADE in the assessment of sinonasal lesions and compare the quality of TGSE BLADE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The difference of ADC among 3 DWIs may be mainly caused by the differences of susceptibility artifacts appeared in each DWI. Susceptibility artifact in SS-EPI DWI and RESOLVE DWI was more severe than that in TGSE-BLADE DWI, which suggests that susceptibility artifacts affected calculation of ADC largely in SS-EPI DWI and RESOLVE DWI 24 . However, the ICC of ADC values among the three DWIs indicates an almost perfect agreement.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The difference of ADC among 3 DWIs may be mainly caused by the differences of susceptibility artifacts appeared in each DWI. Susceptibility artifact in SS-EPI DWI and RESOLVE DWI was more severe than that in TGSE-BLADE DWI, which suggests that susceptibility artifacts affected calculation of ADC largely in SS-EPI DWI and RESOLVE DWI 24 . However, the ICC of ADC values among the three DWIs indicates an almost perfect agreement.…”
Section: Discussionmentioning
confidence: 93%
“…There was less difference in distortion between TGSE-BLADE DWI and the other DWI sequences with increasing distance from air–bone interfaces (e.g., occipital lobe and parietal lobe). Most previous studies have performed qualitative evaluation of distortion 20 , 23 , 24 . In the present study, however, we demonstrated quantitatively that distortion was reduced in intracranial regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, TGSE BLADE DWI was shown to significantly reduce distortion, blurring, and magnetic-sensitive artifacts (10). This technique has been used to visualize orbital tumors, cerebellopontine angle tumors, and sinonasal lesions on 3T magnetic resonance images (MRI) (11–13). Recently, it has been confirmed that TGSE BLADE DWI possesses superior image quality in cholesteatoma imaging and may have a unique role in identifying particularly small cholesteatomas (14).…”
mentioning
confidence: 99%